(untitled) (Proceedings of the International Conference on Public Health, 2022)
Helminthiasis is one of the parasitic diseases that infect the human intestines due to poor personal hygiene and sanitation which mostly occurs in children and affects their development and performance. The use of audio-visual media to educate the children at risk should help the transfer of knowledge with simpler information and more attractive approach. This study aims to obtain the insight of responses from elementary school students as the target audience in absorbing the information about Helminthiasis prevention through audio-visual media. An observational study with a qualitative approach was carried out at Elementary School Number 3 Blahkiuh, Abiansemal sub-district, Bali, in December 2021. 80 students from grades 1, 2, and 3 that were involved in health education were directly observed. The observations utilized a checklist that assessed the student’s capability to mention, explain, and define the information themselves, along with examples. Information regarding the cause, transmission, impact, and prevention of helminthiasis was delivered using a three minutes animated video. The observation shows that the use of animated video in the dissemination of health information to students in grades 1, 2, and 3 provides a good response from them in terms of their interest in the topic and media along with their active engagement in learning and receiving information related to Helminthiasis prevention. Delivering information through animated video to students in grades 1, 2, and 3 as a group in the early stage of school provide to be beneficial for the increasing student’s knowledge of new health information with an attractive approach.